The nucleic acid‐sensing inflammasomes. Issue 1 (May 2015) - Xiao, Tsan Sam
Summary: Inflammasomes are oligomeric signaling complexes that promote caspase activation and maturation of proinflammatory cytokines. Structural and biophysical studies have shed light on the mechanisms of nucleic acid recognition and signaling complex assembly involving the AIM2 (absent in myeloma 2) and IFI16 (γ‐interferon‐inducible protein 16) inflammasomes. However, our understanding of the mechanisms of the NLRP3 (nucleotide‐binding oligomerization‐like receptor family, pyrin domain‐containing protein 3) activation, either by nucleic acids or by other reported stimuli, has remained elusive. Exciting recent progress on the filament formation by the ASC (apoptosis‐associated speck‐like protein containing a caspase recruitment domain) pyrin domain and the IFI16–double stranded DNA complex has established that the formation of higher order polymers is one of the general mechanisms for signaling platform assembly in innate immune system. The paradigm‐changing discovery of the extracellular function of the NLRP3–ASC inflammasome has opened the door for therapeutic targeting the inflammasome filament formation for various clinical conditions. Future characterization of the canonical and non‐canonical inflammasome complexes will undoubtedly reveal more surprises on their structure and function and enrich our understanding of the molecular mechanisms of ligand recognition, activation, and regulation.